Antimicrobial activity of Lactobacillus spp. isolated from fermented foods and their inhibitory effect against foodborne pathogens - Athraa Oudah Hussein; Khalida Khalil; Nurul Aqilah Mohd Zaini; Ahmed Khassaf Al Atya; Wan Syaidatul Aqma (PeerJ)
Lactic acid bacteria (LAB), known for their health benefits, exhibit antimicrobial and antibiofilm properties. This study investigated the cell-free supernatant (CFS) of Lactobacillus spp., particularly L. plantarum KR3, against the common foodborne pathogens S. aureus, E. coli and Salmonella spp. Lactobacillus strains were isolated from cheese, pickles and yoghurt. They were then identified by morphological, physiological and biochemical characteristics and confirmed by 16S rRNA gene sequencing. Culture supernatants from seven lactobacilli isolates showed varying inhibitory activities. Notably, L. plantarum KR3 and L. pentosus had the highest bacteriocin gene counts. L. plantarum KR3 CFS demonstrated significant antibacterial activity, with inhibition zones of 20 ± 0.34 mm for S. aureus, 23 ± 1.64 mm for E. coli, and 17.1 ± 1.70 mm for Salmonella spp. The CFS also exhibited substantial antibiofilm activity, with 59.12 ± 0.03% against S. aureus, 83.50 ± 0.01% against E. coli, and 60. ± 0.04% against Salmonella spp., which were enhanced at the minimum inhibitory concentration (MIC). These results highlighted the potential of L. plantarum KR3 in antimicrobial applications, however, further research is needed to evaluate its viability and functional properties for probiotic use. Additionally, the CFS demonstrated exceptional thermal stability, reinforcing its promise as an antimicrobial agent.